Life cycle cost estimation and environmental valuation of coal mine tailings management - Adiansyah, Joni Safaat; Rosano, Michele; Biswas, Wahidul; Haque, N. (2017)
Sustainable mining management is increasingly seen as an important issue in achieving a social license to operate for mining companies. This study describes the life cycle cost (LCC) analysis and environmental valuation for several coal mine tailings management scenarios. The economic feasibility of six different options was assessed using the Net Present Value (NPV) and Benefit-Cost Analysis (BCA) methods. These options were belt press (OPT 1), tailings paste (OPT 2), thickened tailings (OPT 3), and OPT 1 with technology improvement and renewable energy sources (OPT 1A-C). The results revealed that OPT 1A (belt press technology with stack cell flotation) was the first preference in terms of LCC while OPT 1C (belt press technology with stack cell flotation and 10% wind energy) generated the highest benefits value (BCA) compared to the other options. The LCC and BCA components and the volume of GHG emissions were used to determine the best option. Normalization of these three elements resulted in the selection of Option 1C as being the most cost-effective option.